A negative breakdown test in a fragrance mix I‐positive patient does not rule out contact allergy to its fragrance constituents. (1st March 2021) - Geier, Johannes; Schubert, Steffen; Schnuch, Axel; Szliska, Christiane; Weisshaar, Elke; Kränke, Birger; Werfel, Thomas; Ruëff, Franziska; Schröder‐Kraft, Claudia; Buhl, Timo; ,
Abstract: Background: In about half of the patients reacting positive to fragrance mix I (FM I), breakdown testing remains negative. This raises the question of whether the reaction to FM I is false‐positive, or the breakdown test is false‐negative. Objectives: To identify characteristics and sensitization patterns of patients positive to FM I, but not to its fragrance constituents. Patients and Methods: Retrospective analysis of data from the Information Network of Departments of Dermatology (IVDK) between 2005 and 2019. Three patient groups were defined according to their reaction pattern: Group I, FM I positive and ≥1 single fragrance positive in the breakdown test (n = 1912); Group II, FM I positive and breakdown test negative (n = 1318); Group III, FM I negative (n = 19 790). Results: Regarding the pattern of concomitant reactions to other fragrances, Group II had an intermediate position between Group I and Group III. In other respects (age and sex distribution, frequency of sensitization to non‐fragrance baseline series allergens), Group II rather resembled Group I. Conclusions: Not every positive reaction to FM I in patients with negative breakdown tests is false‐positive. There may be false‐negative reactions to the single fragrance components when patch tested at 1% pet. Raising patch concentrations of some single fragrances is recommended.